Planejamento estratégico: um modelo alternativo para as imobiliárias do Brasil - Alves, Leticia da Costa (2016)
To fit the business environment competitively, companies are looking to develop themselves every time more, adopting strategies, implementing new systems, looking for software to help them and planning strategically how to act in the market. However, in the real estate sector, strategic planning is not widely used or used inefficiently. Thus, this study aims to analyze the characteristics of strategic planning in real estate agencies in Brazil and propose an alternative model of strategic planning for real estate agencies. Therefore, as a methodological procedure a questionnaire was applied in real estate agencies in Brazil, aiming to verify trends that are being used to support the development of the model. It was found that in Brazil real estate agencies using the basic assumptions of strategic planning, but are vulnerable in respect to implementation of the tool and control of the results after the strategic planning. Based on the results, the alternative model of strategic planning proposed for the real estate agencies consists of three main stages: analysis, implementation and control.